تطبيق نموذج التعليم لترقية إنجاز درس اللغة العربية للتلاميذ بمدرسة تراتي المتوسطة الأهلية جرسيك - Marisa, Sofia; Wafa, Ali; Baihaqy, Muhammad (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2017)
The background of this title selection is the inability of students in Arabic. Many students do not like learning Arabic because they feel boredom in learning Arabic. Most students believe that Arabic is a language such a difficult to learn. Among the difficulties faced by students are difficulties in pronounciation and writing. Therefore, researchers want to apply an ASSURE (Analyze State Select Utilize Require Evaluation) to improve student achievement in Arabic. Researchers use quantitative methods and use observation, documentation and tests in their data collection. From the results of the pre-test and post-test conducted by the researcher it can be concluded that there is a significant improvement and shows that the ASSURE (Analyze State Select Utilize Require Evaluation) learning model is effective for use in learning